2006
DOI: 10.1093/ndt/gfl393
|View full text |Cite
|
Sign up to set email alerts
|

Changing prescribing practice in CAPD patients in Korea: increased utilization of low GDP solutions improves patient outcome

Abstract: Prescription of low GDP, pH-neutral PD solutions has rapidly increased in Korea. This change has resulted in a significant improvement in patient and technique survival without any measurable change in peritonitis incidence or rate. Reasons for the improved patient survival cannot be determined from this analysis and require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 18 publications
2
68
0
6
Order By: Relevance
“…These adverse sequelae may be obviated by the administration of commercially available biocompatible PD solutions, characterized by neutral pH and low glucose degradation product (GDP) content. In vitro and ex vivo studies have observed significant improvements in peritoneal membrane cellular function and integrity after exposure to biocompatible solutions compared with conventional solutions (5,(9)(10)(11), and observational cohort studies have reported superior inflammatory marker levels (12), peritonitis and exit site infection rates (13), and patient survival (14)(15)(16). However, these clinical studies were limited by singlecenter design, small patient numbers (12,13), potential indication bias, center effects, and exclusion of patients treated with automatic peritoneal dialysis (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…These adverse sequelae may be obviated by the administration of commercially available biocompatible PD solutions, characterized by neutral pH and low glucose degradation product (GDP) content. In vitro and ex vivo studies have observed significant improvements in peritoneal membrane cellular function and integrity after exposure to biocompatible solutions compared with conventional solutions (5,(9)(10)(11), and observational cohort studies have reported superior inflammatory marker levels (12), peritonitis and exit site infection rates (13), and patient survival (14)(15)(16). However, these clinical studies were limited by singlecenter design, small patient numbers (12,13), potential indication bias, center effects, and exclusion of patients treated with automatic peritoneal dialysis (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…A randomized crossover trial of conventional, acidic, lactate-buffered fluid with pH neutral, lactate-buffered, low GDP fluid in 86 prevalent PD patients demonstrated increases in renal urea and creatinine clearances over a 12-week period. 8 Subsequently, a large, retrospective, observational cohort study in Korea 9,10 demonstrated an association between the use of neutral pH, lactate-buffered, low GDP fluids and superior survival, although this finding was potentially limited by indication bias with residual confounding. 11 Several small, short-term, randomized controlled trials have also reported that neutral pH, low GDP fluids were associated with either a beneficial [12][13][14] or neutral [15][16][17][18][19] effect on residual renal function.…”
mentioning
confidence: 99%
“…In the BALANZ trial, a multicenter, open-labeled, randomized clinical trial of PD patients in Australia and New Zealand, the use of biocompatible compared with conventional PD solutions was associated with a reduction of the overall peritonitis rate (0.30 vs. 0.49 episodes per patient-year) [6]. In contrast, a prospective longitudinal follow-up of almost 4,000 PD patients found no difference in peritonitis rate between newer, biocompatible PD solutions and conventional solutions [7]. In turn, the most recent Cochrane review concluded that there was no significant effect of biocompatible PD solutions on peritonitis rate [8].…”
Section: Introductionmentioning
confidence: 95%